Preparation method and production line of green concrete composite material

By molecular-grade composite of plant fibers with fine-grained cement and rapid carbonization using supercritical carbon dioxide impregnation technology, the problems of limited application range of plant fibers and excessive carbon emissions of industrial materials in the existing technology are solved, and green concrete composite materials with high strength, durability and carbon negative characteristics are achieved, meeting the needs of economic development and emission reduction.

CN114131733BActive Publication Date: 2025-04-25BEIJING JINBO TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111630641.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-28
Publication Date
2025-04-25
Estimated Expiration
2041-12-28

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively utilize plant fibers in agricultural and forestry waste, resulting in limited application scope, and the production of industrial materials leads to excessive carbon emissions, making it difficult to resolve the contradiction between economic development and emission reduction.

Method used

Plant fiber and fine-grinding cement are used as the main raw materials, and the molecular-grade composite of plant fibers and cement materials is achieved through heating crushing, grinding and adjustment of ultrafine powder. Then, supercritical carbon dioxide impregnation technology is used to quickly carbonize to prepare green concrete composite materials.

Benefits of technology

The high strength, durability and carbon negative characteristics of green concrete composite materials are achieved, and can effectively replace steel, aluminum alloy and plastic products, reduce carbon dioxide emissions, and solve the contradiction between economic development and emission reduction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114131733B_ABST
    Figure CN114131733B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and production line of a green concrete composite material. The invention uses renewable plant fiber and large-scale industrially produced ground cement as main raw materials, and uses additives, high-efficiency water reducing agent, and ultrafine powder for adjustment. In the preparation process, the additive is first added when the plant fiber is dissociated to obtain mechanical pulp, and then the mechanical pulp and the ground cement are mixed in a mill and a high-efficiency water reducing agent is added to obtain fiber cement slurry, and then ultrafine powder is added for adjustment and molding to obtain standard plates, pipes and profiles and non-standard parts, and then the green concrete prefabricated parts are quickly carbonized by supercritical carbon dioxide impregnation treatment in a carbonization kettle, and finally the surface is trimmed and anti-corrosion and wear-resistant treatment is performed to obtain green concrete composite material products. The invention can realize industrial-scale preparation of green concrete composite materials, which have the characteristics of high strength, durability and processability, and can also fix more than 0.35 tons of carbon per ton, and can replace metals and plastics on a large scale, reducing emissions by more than 2 tons per ton.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of composite materials, and more specifically, to a preparation method and production line of green concrete composite materials. Background Art

[0002] Every year, more than 150 billion tons of plant fiber are produced by photosynthesis on the earth. Human agricultural and industrial activities also generate a large amount of agricultural and forestry waste every year. Among them, wheat straw, rice straw, bamboo and wood waste are mainly composed of plant fiber, with an annual global output of more than 3 billion tons. Most of the agricultural and forestry waste is piled outside the farmland and burned or rotted. Some of it is directly returned to the field. The pollution caused by burning and returning to the field affects farmland operations and soil ecology. The main treatment method is to degrade naturally after storage, which is also an important part of the carbon dioxide cycle in the atmospheric environment. As a renewable natural polymer material, there is no good large-scale industrial utilization technology except natural degradation. The wheat straw, rice straw, bamboo and wood waste in agricultural and forestry waste has a high content of plant fiber, including more than 90% of cellulose, hemicellulose and lignin, which is an excellent renewable polymer material. The current utilization rate is still very low. The current industrial application is mainly straw pulp papermaking, fiber density board, fiber cement board, etc., accounting for less than 1% of the total.

[0003] With the development of human society and economy and the progress of industrial technology, the demand for industrial materials has increased dramatically. The production of man-made panels, pipes and profiles mainly composed of metals and plastics has also increased. Metals and plastics are high-carbon materials, resulting in the accumulation of carbon emissions close to the critical value of atmospheric warming. China's production capacity of crude steel, electrolytic aluminum, cement and plastic materials accounts for more than 50% of the world's total. At the same time, China's carbon emissions account for more than 30%, which has caused an irreconcilable contradiction between China's economic development and emission reduction. The development of negative carbon materials is the inevitable way to reduce the production capacity of industrial materials and promote social and economic development. At present, it is possible to Regenerated natural plant fiber materials have become the first choice. In addition to straw pulp papermaking, fiber density boards and fiber cement boards with plant fibers as the main raw materials are also common in the market. Although these two materials are produced on an industrial scale and the applied products are limited to boards, their overall application is also limited to decoration and decoration projects. The main reason is that the performance of the materials cannot meet higher requirements. For example, the strength, water resistance, fire resistance, UV resistance, wear resistance, impact resistance and other properties are still very low, and the service life is generally not more than 15 years, and it is impossible to replace steel, aluminum alloy and plastic materials in the form of boards, pipes and profiles.

[0004] How to develop composite materials that can replace steel, aluminum alloys and plastic products is the key to solving the current social and economic development and emission reduction. In particular, the large-scale industrial application of plant fibers to produce composite materials that can replace metals and plastics can not only reduce carbon dioxide emissions from natural degradation, but also greatly reduce the large amount of carbon dioxide emitted by the production of metals and plastics. It is an important way to resolve the contradiction between emission reduction and development. Summary of the invention

[0005] An object of the present invention is to solve at least the above problems and to provide at least the advantages which will be described hereinafter.

[0006] The invention uses renewable plant fiber and ground cement that is being industrially produced on a large scale as main raw materials, and uses additives, high-efficiency water reducing agent and ultrafine powder for adjustment. Firstly, a wood pulp machine is used to heat, crush and semi-dissociate the plant fiber. During the dissociation process, calcium magnesium sodium salt of sulfuric acid or sulfurous acid is added as an additive to obtain mechanical pulp. Then, the mechanical pulp and the ground cement are mixed in a grinder and a high-efficiency water reducing agent is added to grind the plant fiber and fully disperse and mix with the ground cement-based material to achieve high-proportion molecular-level compounding. Ultrafine powder and graded fine sand are added to the prepared fiber cement slurry in a mixer, and the water content is adjusted to obtain green concrete slurry. The green concrete slurry is vacuum-formed in an extruder or a pressure-vibration integrated machine to obtain green concrete prefabricated parts, including standard plates, pipes and profiles, as well as non-standard special-shaped parts and components. Then, supercritical carbon dioxide impregnation treatment is used to quickly carbonize the green concrete prefabricated parts. Finally, the carbonized green concrete prefabricated parts are surface-finished and wear-resistant and anti-corrosion treated to obtain green concrete composite material products. The present invention can realize the industrial-scale preparation of green concrete composite materials. This material not only has the characteristics of high strength, durability and processability, but also has negative carbon properties, which may effectively solve the contradiction between economic development and carbon emissions in important material industries.

[0007] One purpose of the present invention is to utilize physical dispersion and chemical composite technology to molecular-level composite plant fiber and cement material, and then use supercritical carbonization impregnation technology to improve the density of the material and quickly complete hardening, so that the plant fiber is permanently enclosed in the cement-based material. The outer layer deepening treatment technology used makes the surface of the composite material denser and increases functionality. The final green concrete composite material standard products and non-standard parts have the appearance of metal and ceramic materials, exceeding the specific strength of aluminum alloy, comparable to the durability of ceramics, and exceeding the toughness of plastics. This green concrete composite material that combines the toughness of plant fiber and the rigidity of cement material has high strength, good durability, higher density, good processability, and has the comprehensive performance of replacing steel, aluminum alloy and plastic products. Supercritical carbonization technology shortens the production cycle of this material from one month to one day, laying a sufficient foundation for large-scale industrial production.

[0008] Another purpose of the present invention is to manufacture industrial materials for carbon fixation. The green concrete composite material of the present invention is different from traditional materials in that the green concrete composite material uses plant fibers and supercritical carbonization to fix and seal a large amount of carbon dioxide. Each ton of green concrete composite material can solidify and seal more than 0.35 tons of carbon dioxide. It is a veritable negative carbon material. It can replace metal and plastic products on a large scale in the fields of building materials engineering, machinery manufacturing, infrastructure, etc., thereby greatly reducing the large amount of carbon dioxide emitted during the production of metals and plastics. The green concrete composite material launched in this project has low raw material cost, high product added value, and a wide range of applications. Its industrial-scale promotion and application can effectively solve the contradiction between emission reduction and development. After large-scale replacement of metals and plastics, emissions can be reduced by more than 2 tons per ton.

[0009] In order to achieve these purposes and other advantages according to the present invention, a green concrete composite material and a preparation method thereof are provided, which include the following steps:

[0010] Step 1, adding 15 to 45 parts by weight of plant fiber raw materials and 0.3 to 7.5 parts by weight of additives into a wood pulp machine, heating, crushing and grinding to semi-dissociate the plant fibers to obtain mechanical pulp;

[0011] Step 2: adding the mechanical pulp obtained in step 1, 25 to 57 parts by weight of ground cement and 0.3 to 9.5 parts by weight of high-efficiency water reducing agent into a wet mill, mixing, heating and grinding to separate the plant fibers and disperse them in the ground cement slurry to obtain fiber cement slurry;

[0012] Step 3: Extruding or vibrating the fiber cement slurry obtained in step 2 to form green concrete prefabricated parts, including standard plates, pipes and profiles, as well as non-standard special-shaped parts and components, and then autoclaving and curing the green concrete prefabricated parts;

[0013] Step 4: placing the green concrete prefabricated part obtained in step 3 in a carbonization kettle for vacuum degassing and dehydration, and then impregnating and carbonizing with supercritical carbon dioxide, and carbon dioxide is cyclically carbonized to reduce air emissions and improve efficiency;

[0014] Step 5: Take out the carbonized green concrete prefabricated parts from the carbonization kettle, grind and trim them, and spray anti-corrosion and wear-resistant materials on the surface of the green concrete prefabricated parts.

[0015] Preferably, during the processing of step 2, 15 to 35 parts by weight of ultrafine powder is added to the wet grinder to adjust the moisture content for easy molding.

[0016] A preparation method closer to the present invention also needs to adopt the following steps:

[0017] Step 1, adding 15 to 45 parts by weight of plant fiber raw materials and 0.3 to 7.5 parts by weight of additives into a wood pulp machine, heating, crushing and grinding to semi-dissociate the plant fibers to obtain mechanical pulp;

[0018] Step 2: adding the mechanical pulp obtained in step 1, 25 to 57 parts by weight of ground cement and 0.3 to 9.5 parts by weight of high-efficiency water reducing agent into a wet mill, mixing, heating and grinding to separate the plant fibers and disperse them in the ground cement slurry to obtain fiber cement slurry;

[0019] Step 3: Add the fiber cement slurry obtained in step 2, 15 to 35 parts by weight of ultrafine powder, and 5 to 25 parts by weight of graded fine sand into a high-powered mixer, and heat and stir to obtain green concrete slurry;

[0020] Step 4: forming the green concrete slurry obtained in step 3 into green concrete prefabricated parts, including standard types of plates, pipes and profiles and non-standard parts, and then autoclaving and curing the green concrete prefabricated parts;

[0021] Step 5: placing the green concrete prefabricated part obtained in step 4 in a carbonization kettle for vacuum degassing and dehydration, and then impregnating and carbonizing with supercritical carbon dioxide;

[0022] Step 6: Take out the carbonized green concrete prefabricated parts from the carbonization kettle, grind and trim them, and spray anti-corrosion and wear-resistant materials on the surface of the prefabricated parts.

[0023] In the above processing steps, the present invention selects raw materials with high plant fiber content, including at least one of wheat straw, rice straw and bamboo waste, the additive is a sulfite solution containing at least one of calcium, magnesium, sodium and ammonia, and modifiers and activators are added during grinding, the mixing ratio of the modifiers and the activators is 1:0.3-3.4, and the specific surface area of ​​the ground cement is not less than 350m 2 / Kg;

[0024] Preferably, during the processing of step 1, the heating temperature is 75-165° C., the crushing and grinding time is no more than 2 hours, quicklime is added to the wood pulp machine during the heating, crushing and grinding, and the pH value in the wood pulp machine is adjusted to 7.5-11;

[0025] Preferably, during the processing of step 2, the heating temperature is 75-165° C. and the grinding time does not exceed 2.5 hours.

[0026] Preferably, in order to adjust the moisture content, utilize environmentally friendly materials and improve performance, the specific surface area of ​​the ultrafine powder is greater than 450 m 2 / Kg, the ultrafine powder is at least one of silica ash, slag ultrafine powder and steel slag ultrafine powder. When the ultrafine powder contains both slag ultrafine powder and steel slag ultrafine powder, the mass ratio of slag ultrafine powder to steel slag ultrafine powder is 1:0.5-2.

[0027] The present invention can also reduce the proportion of cement in the formula, wherein part of the ground cement is replaced by an equal amount of metakaolin, and the fineness of the metakaolin is greater than 400 meshes.

[0028] In the processing of the present invention, in order to make the plant fiber have better tensile properties, the first step of the present invention is to adopt a circulation or multi-stage treatment process to open the cell wall where the plant fiber is located, and to incompletely separate the cellulose, hemicellulose and lignin, wherein the maximum diameter of the cellulose does not exceed 0.3 mm, and the dissolution rate of the lignin does not exceed 30%.

[0029] Preferably, after adding the stirring equipment, during the processing of step three, the heating temperature of the heating and stirring is above 95°C, during the processing of step four, the heating temperature of the green concrete slurry during prefabrication is above 75°C, and the heating temperature of the prefabricated parts during autoclaving and curing is above 85°C.

[0030] The preparation method of the green concrete composite material of the present invention includes, but is not limited to, a production line of the following equipment, a wood pulp machine for preparing mechanical pulp, a centrifugal mill or a vibration mill for preparing fiber cement slurry, equipment for preparing green concrete prefabricated parts, a high-pressure autoclave for autoclaving and curing of prefabricated parts, a carbonization autoclave for supercritical carbon dioxide impregnation treatment of prefabricated parts, and a grinding and spraying equipment for surface treatment;

[0031] Among them, the equipment for preparing green concrete prefabricated parts is provided with a vacuum system, and the vacuum system is connected to the material molding chamber of the equipment for preparing green concrete prefabricated parts, so that the material is prefabricated and molded under a vacuum state. The equipment for preparing green concrete prefabricated parts is a pipe extruder or a profile extruder or a plate pressing and vibrating integrated machine for standard prefabricated parts and a mold extrusion or pressing and vibrating integrated molding machine for non-standard prefabricated parts.

[0032] The method for preparing the green concrete composite material of the present invention is preferred, including but not limited to the production line of the following equipment, a wood pulp machine for preparing mechanical pulp, a centrifugal mill or a vibration mill for preparing fiber cement slurry, a powerful mixer for preparing green concrete slurry, equipment for preparing green concrete prefabricated parts, an autoclave for autoclaving and curing of prefabricated parts, a carbonization kettle for supercritical carbon dioxide impregnation treatment of prefabricated parts, and a grinding and spraying equipment for surface treatment;

[0033] Among them, the equipment for preparing green concrete prefabricated parts is provided with a vacuum system, and the vacuum system is connected to the material molding cavity of the equipment for preparing green concrete prefabricated parts for vacuum prefabrication and molding. The equipment for preparing green concrete prefabricated parts is a pipe extruder or a profile extruder or a plate pressing and vibrating integrated machine for standard prefabricated parts and a mold extrusion or pressing and vibrating integrated machine for non-standard prefabricated parts.

[0034] The green concrete composite material and its preparation method and production line of the present invention have at least the following beneficial effects:

[0035] The function of step one is to use a wood pulp machine to dissociate the plant fiber but the cellulose, hemicellulose and lignin in the plant fiber cannot be completely separated, which is referred to as semi-dissociation. By adding sulfate or sulfite of calcium magnesium sodium ammonia as an additive, and controlling the temperature, time and pH value during the dissociation process, in the process of crushing, heating and dissociation, the cell wall must be opened to allow the plant fiber diameter to reach a certain fineness, and the cellulose, hemicellulose and lignin of the plant fiber must be partially chemically linked but cannot be completely separated. The method of controlling the parameters to only break a part of the chemical bonds of the three is to control the solubility of each component to not exceed 30%, and keep the temperature not lower than 75°C to straighten the cellulose, while the hemicellulose and lignin connected to the cellulose are opened, the active end is connected to the sulfonic acid group and the modified group, has hydrophilicity, and is conducive to connecting with the active end of the inorganic material. In the above processing steps, the present invention determines that the plant fiber raw material is at least one of wheat straw, rice straw and bamboo and wood waste.

[0036] The function of step 2 is to grind the plant fiber in the mill to continue to separate and disperse it in the cement-based material. In the process of mixing and stirring with the cement-based material, a high-efficiency water reducer is added to improve the dispersion of cellulose in the plant fiber and compound it with the active base of the cement-based material. The active ends of hemicellulose and lignin linked to cellulose continue to compound with the active ends of the cement-based material, and the temperature and time are controlled to make the active end of lignin and the active end of the cement material have a higher compounding rate. The cellulose is straightened and is in a three-dimensional stacking state in the cement-based material. The mixed heating and grinding make the plant fiber more evenly dispersed in the ground cement to prepare fiber cement slurry. In order to increase the dispersibility of the plant fiber in the cement-based material, a modifier and an active agent are added during the grinding. The mixing ratio of the modifier and the active agent is 1:0.3-3.4, and the specific surface area of ​​the ground cement is not less than 350m 2 / Kg.

[0037] The purpose of step three is to effectively adjust the moisture content of the fiber cement slurry by adding the ultrafine powder and graded fine sand in the mixer to facilitate molding. In order to increase the use of environmentally friendly materials and not affect the performance of green concrete composite materials, it is clear that the specific surface area of ​​the ultrafine powder is greater than 450m 2 / Kg, the ultrafine powder is at least one of silica ash, slag ultrafine powder and steel slag ultrafine powder. When the ultrafine powder contains both slag ultrafine powder and steel slag ultrafine powder, the mass ratio of slag ultrafine powder to steel slag ultrafine powder is 1:0.5-2. At the same time, the rigidity of the material is improved and the cost is reduced by grading fine sand. The prepared green concrete slurry has better plasticity and is easy to shape. Of course, when there is no need to add graded fine sand, and some materials that do not require high performance are produced, this step can be combined with step two, which can also save investment costs and improve production efficiency.

[0038] The role of step four is to prepare green concrete prefabricated parts, including standard models of plates, pipes and profiles and non-standard models of parts, and then put the green concrete prefabricated parts into an autoclave for steam curing, so that the prefabricated parts can be quickly hardened and the manufacturing cycle can be shortened. During the molding process, the material molding cavity is connected to the vacuum system, which can effectively remove the air in the prefabricated parts, reduce the porosity and increase the density, thereby effectively improving the strength of the green concrete composite material. The present invention can effectively solve the uncertainty of cement-based materials, especially ordinary concrete engineering, for production through the large-scale production of standard parts and non-standard parts. By changing engineering materials into standard materials, the production of green concrete composite materials can be factory-based and scaled, which is the premise of large-scale industrial application.

[0039] The role of step five is to use supercritical carbon dioxide to quickly carbonize the green concrete prefabricated parts, because supercritical carbon dioxide is more than 100 times more permeable than ordinary gases and liquids. Using vacuum degassing and dehydration before carbonization can effectively improve the carbonization efficiency and reduce the influence of water vapor and air on supercritical carbon dioxide. The carbonized green concrete composite material has a density comparable to that of metals and plastics, and has three major functions: one is that the strength can be increased by more than 50%, and the other is that the plant fiber can be completely enclosed in the material, which basically solves the oxidation and degradation loss of biomaterials and makes the life of the material reach more than 100 years. There is also a more important role. Through the rapid carbonization of supercritical carbon dioxide, the hardening time of cement-based materials can be shortened from 75% of 28 days to more than 85% of 3 hours, that is, the manufacturing cycle is shortened from one month to 1 day. This is a revolutionary progress for the large-scale production of industrial materials and is also the key to large-scale industrial production of green concrete materials.

[0040] The purpose of step six is ​​to make the outer layer of the green concrete material denser and more functional, so that it can have the appearance of metal or ceramic materials. At the same time, through the grinding and finishing of the carbonized material and the deepening treatment of the outer layer, including PVD, electrostatic, ion spraying anti-corrosion and wear-resistant materials, the green concrete can be made denser, more sealed to biological materials, more functional, more beautiful, and more durable.

[0041] From the above description, it can be seen that in the preparation method and production line of the green concrete composite material of the present invention, the above steps and the main equipment in the production line are indispensable. The production line composed of the equipment proposed in the present invention is an important equipment for preparing green concrete composite materials. At the same time, through the organic combination of these equipments, the green concrete composite material and the plant fiber materials and cement-based materials on the market currently have revolutionary changes in performance, which not only realizes large-scale carbon fixation and is a veritable negative carbon material, but also has the excellent performance of large-scale replacement of metals and plastics, and can also achieve large-scale emission reduction, which can effectively solve the contradiction between economic development and emission reduction.

[0042] Other advantages, objectives and features of the present invention will be embodied in part through the following embodiments, and will also be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 It is a schematic diagram of the preparation steps and production line of the present invention;

[0044] Figure 2 The schematic diagram is for adding a stirring step and equipment in the preparation of the present invention. DETAILED DESCRIPTION

[0045] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.

[0046] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials are commercially available unless otherwise specified; in the description of the present invention, the terms "lateral", "longitudinal", "upper", "lower", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0047] Example 1: According to the green concrete composite material and its preparation method and production line provided by the present invention, the green concrete composite material is prepared according to the following steps. The green concrete composite material production line used in this example includes a wood pulp machine for preparing mechanical pulp, a centrifugal mill or a vibration mill for preparing fiber cement slurry, equipment for preparing green concrete prefabricated parts (a pipe extruder or a profile extruder or a plate pressure-vibration integrated machine for standard product prefabricated parts), a high-pressure autoclave for autoclaving and curing of prefabricated parts, and a carbonization autoclave for supercritical carbon dioxide impregnation treatment of prefabricated parts. The green concrete composite material and its preparation method include the following steps, such as Figure 1 As shown:

[0048] Step 1, adding 35 parts by weight of plant fiber raw material and 3.5 parts by weight of additives into a wood pulp machine, heating, crushing and grinding to semi-dissociate the plant fiber to obtain mechanical pulp, the plant fiber is chopped with wheat straw, the additive is a mixture of calcium sulfite and sodium sulfite in a ratio of 1:1 to reduce the use of sodium, the heating temperature during dissociation is 150°C, the crushing and dissociation time is 1h, a container is added in parallel with the wood pulp machine, a circulating treatment process is adopted, and the cell wall where the plant fiber is located is opened by controlling the time, temperature and pH value, and the cellulose, hemicellulose and lignin are not completely separated, wherein the maximum diameter of cellulose does not exceed 0.3mm, and the dissolution rate of lignin does not exceed 30%;

[0049] Step 2: Add the mechanical pulp obtained in step 1, 47 parts by weight of ground cement and 2.5 parts by weight of high-efficiency water reducing agent into a wet centrifugal mill or a vibration mill, mix, heat and grind to modify the plant fiber and the ground cement to obtain fiber cement slurry. The high-efficiency water reducing agent is a polycarboxylic acid water reducing agent with a concentration of 25%, a heating temperature of 145°C, a grinding time of 1.5h, and ultrafine powder with a specific surface area of ​​550m2 is added at a later stage. 2 / Kg, the ultrafine powder is a mixture of silica fume, slag ultrafine powder and steel slag ultrafine powder, the proportion of ingredients is 1:1:1, and the moisture content is less than 18%;

[0050] Step 3: forming the fiber cement slurry obtained in step 2 into green concrete prefabricated parts, including standard-type plates, pipes and profiles and non-standard-type parts, and then autoclaving and curing the green concrete prefabricated parts;

[0051] Step 4: Place the preform obtained in step 3 in a carbonization kettle for vacuum degassing and dehydration, and then use supercritical carbon dioxide for impregnation and carbonization. The vacuum pressure is controlled at 0.05 MPa. The supercritical carbon dioxide adopts a circulation device to increase the reuse rate of carbon dioxide.

[0052] Step 5: Take out the carbonized green concrete prefabricated parts from the carbonization kettle, grind and trim them, and then electrostatically spray anti-corrosion and wear-resistant materials on the surface of the prefabricated parts.

[0053] The green concrete composite material sample prepared by Example 1 has a carbon fixation of 0.38 tons per ton, which has exceeded the standard of negative carbon materials. The compressive strength of the prepared profile exceeds 350MPa, and the tensile strength is not less than 50% of the compressive strength. The strength reaches the aluminum alloy standard. The durability has been tested by freeze-thaw, ultraviolet, rain, salt spray and other tests of impermeability, freeze-thaw resistance, and sulfate corrosion resistance. The impermeability grade reaches P15, and the mass loss rate is less than 0.02% after 300 freeze-thaw cycles. The mass loss is less than 0.1% after 80 salt spray test cycles. These indicators far exceed high-performance concrete, and the pressure resistance of the prepared sealed container reaches the standard of ordinary PVC. (This embodiment and the following embodiments and comparative examples all adopt the strength detection standard "Concrete Strength Inspection and Evaluation Standard" B / T50107-2010, the durability detection standard "Concrete Durability Inspection and Evaluation Standard" JGJ@T193-2009, and the salt spray detection standard "Salt Spray Test National Standard" GB6458-86)

[0054] Example 2, on the basis of Example 1, during the crushing and dissociation in step 1, quicklime is added at 40 minutes of crushing and dissociation, and the pH value in the wood pulp machine is adjusted to 7.5-11; during the grinding in step 2, a modifier and an activator are also added, the mixing ratio of the modifier and the activator is 1:1, and the total weight of the modifier and the activator is 4.5 parts;

[0055] The green concrete composite material sample prepared by Example 2 is calculated to have a carbon fixation of 0.4 tons per ton, which exceeds the standard of negative carbon materials. The compressive strength of the prepared profile exceeds 360 MPa, and the tensile strength is not less than 60% of the compressive strength. The strength reaches the aluminum alloy standard, and the durability has been tested by freeze-thaw, UV, rain, salt spray and other tests of impermeability, freeze-thaw resistance, and sulfate corrosion resistance. The impermeability grade reaches P15, 300 freeze-thaw cycles, and the mass loss rate is less than 0.02%. The salt spray test cycle is 80 times, and the mass loss is less than 0.1%. These indicators far exceed high-performance concrete, and the pressure resistance of the prepared sealed container reaches the standard of ordinary PVC.

[0056] Example 3: According to the green concrete composite material and its preparation method and production line provided by the present invention, a green concrete composite material with higher rigidity is prepared according to the following steps. The production line of the green concrete composite material used in this example includes a wood pulp machine for preparing mechanical pulp, a centrifugal mill or a vibration mill for preparing fiber cement slurry, a high-power mixer for preparing green concrete slurry, equipment for preparing green concrete prefabricated parts (a pipe extruder or a profile extruder or a plate pressure-vibration integrated machine for standard product prefabricated parts), a high-pressure autoclave for autoclaving and curing of green concrete prefabricated parts, and a carbonization autoclave for supercritical carbon dioxide impregnation treatment of green concrete prefabricated parts. The green concrete composite material and its preparation method include the following steps, such as Figure 2 As shown:

[0057] Step 1, adding 35 parts by weight of plant fiber raw material and 3.5 parts by weight of additives into a wood pulp machine, heating, crushing and grinding to semi-dissociate the plant fiber to obtain mechanical pulp, the plant fiber is chopped wheat straw, the additive is a mixture of calcium sulfite and sodium sulfite in a ratio of 1:1 to reduce the amount of sodium used, and other parameters are implemented according to Example 1;

[0058] Step 2: Add the mechanical pulp obtained in step 1, 47 parts by weight of ground cement and 2.5 parts by weight of high-efficiency water reducing agent into a wet centrifugal mill or a vibration mill, mix, heat and grind to modify the plant fiber and the ground cement to obtain fiber cement slurry, wherein the modifier is a silane coupling agent, and the other parameters are carried out according to Example 1;

[0059] Step 3: Add the fiber cement slurry obtained in step 2, 17 parts by weight of ultrafine powder, and 15 parts by weight of graded fine sand into a powerful mixer, and adjust the moisture content to less than 20%. Heat and stir to obtain green concrete slurry. During the stirring process, the heating temperature is greater than 98°C, and other parameters are implemented as in Example 1;

[0060] Step 4: The green concrete slurry obtained in step 3 is molded into green concrete prefabricated parts, including standard plates, pipes and profiles as well as non-standard special-shaped parts and components. During the processing, the heating temperature of the green concrete slurry during prefabrication is 85° C., and then the green concrete prefabricated parts are autoclaved and cured. The heating temperature of the prefabricated parts during autoclaving is 85° C.;

[0061] Step 5: placing the green concrete prefabricated part obtained in step 4 in a carbonization kettle for vacuum degassing and dehydration, and then impregnating and carbonizing with supercritical carbon dioxide;

[0062] Step 6: Take out the carbonized green concrete prefabricated parts from the carbonization kettle, grind and trim them, and then spray the surface of the prefabricated parts with anti-corrosion and wear-resistant materials;

[0063] The above steps are improved with reference to Example 1, and the same steps and data are referred to Example 1.

[0064] In Example 3, for comparison, wheat straw is still selected as the plant fiber, and the ultrafine powder is selected from the same materials and proportions as in Example 1. The prepared green concrete composite material sample has a carbon fixation of 0.42 tons per ton, which exceeds the standard of negative carbon materials. The prepared profile has a compressive strength of 360 MPa, and the tensile strength exceeds the compressive strength by 40%, and the strength is close to the aluminum alloy standard. The durability has been tested through multiple tests such as freeze-thaw, UV, rain, salt spray, etc., for impermeability, frost resistance, and erosion resistance. The results are close to those in Example 1, reaching the standard of high-performance concrete, and the pressure-resistant sealing performance of the prepared sealed container reaches the standard of ordinary PVC.

[0065] Example 4, on the basis of Example 3, during the crushing and dissociation in step 1, quicklime is added at 40 minutes of crushing and dissociation, and the pH value in the wood pulp machine is adjusted to 7.5-11; during the grinding in step 2, a modifier and an activator are also added, the mixing ratio of the modifier and the activator is 1:1, and the total weight of the modifier and the activator is 4.5 parts;

[0066] The green concrete composite material sample prepared in Example 4 has a carbon fixation of 0.43 tons per ton, which exceeds the standard of negative carbon materials. The prepared profile has a compressive strength of 370 MPa, and the tensile strength exceeds the compressive strength by 40%. The strength is close to the aluminum alloy standard. The durability has been tested through multiple tests such as freeze-thaw, UV, rain, salt spray, etc., for impermeability, frost resistance, and erosion resistance. The results are close to those in Example 1, reaching the standard of high-performance concrete. The pressure-resistant and sealing performance of the prepared sealed container reaches the standard of ordinary PVC.

[0067] Example 5, the ground cement was replaced by an equal amount of kaolin. On the basis of Example 2, the cement was replaced by an equal amount of kaolin, the replacement amount was 50%, the fineness of the kaolin was greater than 800 mesh, and all other steps and parameters were referred to Example 2, and all were completed according to the steps of Example 2;

[0068] The green concrete composite material sample prepared by Example 5 has a carbon fixation of 0.36 tons per ton, which exceeds the standard of negative carbon materials. The prepared profile has a compressive strength of 320 MPa, a tensile strength of 55% of the compressive strength, a strength ratio higher than that of Examples 1 and 2, and a strength that reaches the aluminum alloy standard. The durability has been tested through multiple tests such as freeze-thaw, UV, rain, salt spray, etc. for impermeability, frost resistance, and erosion resistance. The comprehensive performance exceeds that of Examples 1 and 3, reaching the standard of high-performance concrete, and the pressure-resistant sealing performance of the prepared sealed container reaches the standard of ordinary PVC.

[0069] Example 6. On the basis of Example 3, following the sequence of the production line disclosed in the present invention, the production line of the green concrete composite material used in the above examples includes a wood pulp machine for preparing mechanical pulp, a centrifugal mill or a vibrating mill for preparing fiber cement slurry, a high-power mixer for preparing green concrete slurry, equipment for preparing green concrete prefabricated parts, a high-pressure autoclave for steam-pressing and curing prefabricated parts, and a carbonization autoclave for supercritical carbon dioxide impregnation treatment of prefabricated parts. In this example, the equipment for preparing green concrete prefabricated parts is connected to the material molding cavity by a vacuum system so that the material is prefabricated and molded under a vacuum state. The equipment for preparing green concrete prefabricated parts is a pipe extruder or a profile extruder or a plate pressure-vibration integrated machine for standard product prefabricated parts, and a mold extrusion or pressure-vibration molding machine for non-standard prefabricated parts. The density of the final sample is increased by 15%, and the strength is increased by 20% compared with the original.

[0070] Comparative Example 1, a fiber density board product with plant fiber as the main raw material and with a large production volume at present, in the instructions for use, the conventional specifications are (length * width): 2440mm*1220mm thickness (height): 6mm 8mm 12mm, 15mm16mm18mm, and the strength indicators are as follows: bending strength, tensile strength, moisture content, nail holding force, water absorption expansion rate and formaldehyde content are all better than GB_T 31765-2015 high-density fiberboard national standard (internal joint strength reaches 0.74Mpa, water absorption thickness expansion rate is less than 3%, and moisture content is about 5%). The maximum strength requirement is 38Mpa, and the actual measured strength is 42Mpa. Compared with the embodiment, the strength indicators differ by an order of magnitude.

[0071] Comparative Example 2, the plant fiber cement material available on the market is a building material developed and produced in the early 1980s to replace asbestos. Due to the many advantages and good quality of this material, it has spread to Australia, America, and Europe. In the United States, it ranks first in sales, with more than three million users and a market share of more than 85%. The most common plant fiber cement siding on the market is made of natural fiber cement (also called strong plant fiber cement), which contains special plant fibers, cement, natural river sand, water and a small amount of chemical additives, and does not contain asbestos, glass fiber and formaldehyde. This product provides physical and chemical properties that are superior to similar products. It has the appearance and excellent properties of wood materials, and is fireproof, non-rotten, and requires almost no maintenance. It is currently mainly used for facade decoration and renovation of villas, factories and residences, building roof decoration, interior wall decoration, suspended ceilings, partitions and retaining walls, indoor and outdoor floor decoration, grille fences and various garden building shapes and accessories. It is mainly used to replace the original wooden boards, PVC hanging boards and other materials to eliminate their shortcomings such as easy aging, mildew, corrosion, and flammability. It has a wide range of uses and is green and environmentally friendly. The bending strength standard requirement of this plant fiberboard is greater than 14MPa. The bending strength of the tested sample is 18MPa. Although it is better than the high-density board material, it is at least an order of magnitude lower than that of metal materials. Compared with the green concrete composite material of the present invention, the present invention not only has a more complicated production process, but also adopts processes such as vacuum forming and supercritical carbonization, and the strength and density are greatly improved. At the same time, after surface treatment, the durability is also greatly improved. It has the strength and processability for manufacturing pipes and profiles, and has the basis and conditions for replacing metal and plastic materials. The plant fiber cement boards currently on the market do not have the basic performance of replacing metals and plastics.

[0072] Comparative Example 3, during the manufacturing process, step 1 of Example 1 did not undergo acid-base control, and the heating temperature was less than 75°C, which was less than the temperature requirement specified in the claims. The strength of the obtained material was slightly higher than that of Comparative Example 2, but much lower than the strength of the green concrete material in Example 1. At the same time, the density was also about 15% lower, and the durability test was significantly reduced. The impermeability grade was P8, and the mass loss rate was less than 0.2% after 300 freeze-thaw cycles. The mass loss was less than 1% after 80 cycles of the salt spray test.

[0073] In Comparative Example 4, the carbonization process in step five of Example 2 is cancelled, and supercritical impregnation is replaced by carbon dioxide gas pressurization. The strength of the obtained material is compared with that of Example 2, and the compressive and tensile strengths are both reduced by about 50%. The durability test is also significantly reduced, the impermeability grade is P13, the mass loss rate is less than 0.5% after 300 freeze-thaw cycles, and the mass loss is less than 2% after 80 cycles of salt spray test.

[0074] Comparative Example 5 is compared with Example 2, the proportion of plant fiber raw materials is reduced to 13 parts by weight, and the proportion of cement is increased by 62 parts by weight. The strength of the obtained material is compared with that of Example 2. The compressive strength remains basically unchanged, the tensile strength decreases by about 30%, and the durability test is also significantly reduced. The impermeability grade is P13, the mass loss rate is less than 0.4% after 300 freeze-thaw cycles, and the mass loss is less than 1.5% after 80 cycles of salt spray test.

[0075] Comparative Example 6 is compared with Example 2. During the processing of step three, the heating temperature of heating and stirring is above 65°C. During the processing of step four, the heating temperature of the green concrete slurry during prefabrication is above 55°C, and the heating temperature of the prefabricated parts during autoclaving is 75°C. The strength of the obtained material is compared with that of Example 2. The compressive strength is basically unchanged, the tensile strength decreases by about 20% on average, the durability test does not change much, the impermeability grade is P14, the mass loss rate is less than 0.02% after 300 freeze-thaw cycles, and the mass loss is less than 0.5% after 80 cycles of salt spray test.

[0076] It can be concluded from the above comparative examples that the green concrete composite material has undergone a large number of tests and optimizations in terms of process steps, proportions and parameter control, and has obvious differences and improvements compared with the preparation and performance of traditional plant fiber composite materials. The present invention not only significantly improves the performance of the material, but also has carbon fixation performance that far exceeds that of traditional materials in terms of carbon fixation weight ratio and carbon fixation time.

[0077] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. A method for preparing a green concrete composite material, characterized in that: The following steps are involved: Step 1, adding 15 to 45 parts by weight of plant fiber raw materials and 0.3 to 7.5 parts by weight of additives into a wood pulp machine, heating, crushing and grinding to semi-dissociate the plant fibers to obtain mechanical pulp; Step 2: adding the mechanical pulp obtained in step 1, 25 to 57 parts by weight of ground cement and 0.3 to 9.5 parts by weight of high-efficiency water reducing agent into a wet mill, mixing, heating and grinding to separate the plant fibers and disperse them in the ground cement slurry to obtain fiber cement slurry; Step 3: forming the fiber cement slurry obtained in step 2 into green concrete prefabricated parts, including standard-type plates, pipes and profiles and non-standard-type parts, and then autoclaving and curing the green concrete prefabricated parts; Step 4: placing the green concrete prefabricated part obtained in step 3 in a carbonization kettle for vacuum degassing and dehydration, and then impregnating and carbonizing with supercritical carbon dioxide; Step 5: Take out the carbonized green concrete prefabricated parts from the carbonization kettle, grind and trim them, and spray anti-corrosion and wear-resistant materials on the surface of the prefabricated parts.

2. The method for preparing the green concrete composite material according to claim 1, characterized in that: During the processing of step 2, 15 to 35 parts by weight of ultrafine powder are also added to the wet grinder.

3. A method for preparing a green concrete composite material, characterized in that: The following steps are involved: Step 1, adding 15 to 45 parts by weight of plant fiber raw materials and 0.3 to 7.5 parts by weight of additives into a wood pulp machine, heating, crushing and grinding to semi-dissociate the plant fibers to obtain mechanical pulp; Step 2: adding the mechanical pulp obtained in step 1, 25 to 57 parts by weight of ground cement and 0.3 to 9.5 parts by weight of high-efficiency water reducing agent into a wet mill, mixing, heating and grinding to separate the plant fibers and disperse them in the ground cement slurry to obtain fiber cement slurry; Step 3: Add the fiber cement slurry obtained in step 2, 15 to 35 parts by weight of ultrafine powder, and 5 to 25 parts by weight of graded fine sand into a high-powered mixer, and heat and stir to obtain green concrete slurry; Step 4: forming the green concrete slurry obtained in step 3 into green concrete prefabricated parts, including standard types of plates, pipes and profiles and non-standard types of parts, and then autoclaving and curing the green concrete prefabricated parts; Step 5: placing the green concrete prefabricated part obtained in step 4 in a carbonization kettle for vacuum degassing and dehydration, and then impregnating and carbonizing with supercritical carbon dioxide; Step 6: Take out the carbonized green concrete prefabricated parts from the carbonization kettle, grind and trim them, and spray anti-corrosion and wear-resistant materials on the surface of the prefabricated parts.

4. The method for preparing the green concrete composite material according to any one of claims 1 to 3, characterized in that: The plant fiber raw material is at least one of wheat straw, rice straw and bamboo waste, the additive is sulfuric acid or sulfite solution containing at least one of calcium, magnesium, sodium and ammonia, and the modifier and the activator are added during grinding, the mixing ratio of the modifier and the activator is 1:0.3-3.4, and the specific surface area of ​​the ground cement is not less than 350m 2 / Kg; During the processing of step 1, the heating temperature is 75-165° C., the crushing and dissociation time is no more than 2 hours, quicklime is added to the wood pulp machine during the heating, crushing and grinding, and the pH value in the wood pulp machine is adjusted to 7.5-11; During the processing of step 2, the heating temperature is 75-165° C., and the grinding time does not exceed 2.5 hours.

5. The method for preparing the green concrete composite material according to claim 2 or 3, characterized in that: The specific surface area of ​​ultrafine powder is greater than 450m 2 / Kg, the ultrafine powder is at least one of silica ash, slag ultrafine powder and steel slag ultrafine powder. When the ultrafine powder contains both slag ultrafine powder and steel slag ultrafine powder, the mass ratio of slag ultrafine powder to steel slag ultrafine powder is 1:0.5-2.

6. The method for preparing the green concrete composite material according to any one of claims 1 to 3, characterized in that: Part of the ground cement is replaced by an equal amount of metakaolin, and the fineness of the metakaolin is greater than 400 mesh.

7. The method for preparing the green concrete composite material according to any one of claims 1 to 3, characterized in that: Step 1 adopts a circulation or multi-stage treatment process to open the cell wall where the plant fiber is located, and the cellulose, hemicellulose and lignin are not completely separated, wherein the maximum diameter of the cellulose does not exceed 0.3mm, and the dissolution rate of lignin does not exceed 30%.

8. The method for preparing the green concrete composite material according to claim 3, characterized in that: During the processing of step three, the heating temperature of heating and stirring is above 95°C. During the processing of step four, the heating temperature of the green concrete slurry during prefabrication is above 75°C, and the heating temperature of the prefabricated parts during autoclaving and curing is above 85°C.

9. A production line using the preparation method according to claim 1 or 2, characterized in that: include: Wood pulping machines for preparing mechanical pulp, centrifugal mills or vibrating mills for preparing fiber cement slurry, equipment for preparing green concrete prefabricated parts, autoclaves for autoclaving and curing of prefabricated parts, carbonizing kettles for supercritical carbon dioxide impregnation treatment of prefabricated parts, and grinding and spraying equipment for surface treatment; Among them, the equipment for preparing green concrete prefabricated parts is provided with a vacuum system, and the vacuum system is connected to the material molding chamber of the equipment for preparing green concrete prefabricated parts, so that the material is prefabricated and molded under a vacuum state. The equipment for preparing green concrete prefabricated parts is a pipe extruder or a profile extruder or a plate pressing and vibrating integrated machine for standard prefabricated parts and a mold extrusion or pressing and vibrating integrated molding machine for non-standard prefabricated parts.

10. A production line using the preparation method as claimed in claim 3, characterized in that: include: Wood pulping machines for preparing mechanical pulp, centrifugal mills or vibrating mills for preparing fiber cement slurry, powerful mixers for preparing green concrete slurry, equipment for preparing green concrete prefabricated parts, autoclaves for autoclaving and curing of green concrete prefabricated parts, carbonizing kettles for supercritical carbon dioxide impregnation treatment of prefabricated parts, and grinding and spraying equipment for surface treatment; Among them, the equipment for preparing green concrete prefabricated parts is provided with a vacuum system, and the vacuum system is connected to the material molding cavity of the equipment for preparing green concrete prefabricated parts to perform vacuum prefabrication and molding. The equipment for preparing green concrete prefabricated parts is a pipe extruder or a profile extruder or a plate pressing and vibrating integrated machine for standard prefabricated parts and a mold extrusion or pressing and vibrating integrated machine for non-standard prefabricated parts.

Citation Information

Patent Citations

  • Preparation method of all-fiber degradable composite material

    CN104497609A

  • Preparation method of super-strong durable material

    CN113715143A